Benefits of ebastine from the position of clinical pharmacology - D. Yu. Ivkin; A. Yu. Grishina; A. G. Petrova; E. V. Moskaleva; N. O. Selizarova (Лечащий Врач, 2023)
The article reviews data on pharmacokinetics, pharmacodynamics, efficacy and safety of ebastine, presents reviews of the most significant clinical trials in the treatment of allergic diseases (allergic rhinitis, urticaria) and comparative studies with other antihistamine drugs available in the arsenal of a modern practical doctor. Data of multiple preclinical and clinical trials presented in domestic and foreign sources allow to demonstrate its effectiveness and safety widely. Ebastin is characterized as medicine with high enough safety profile due to absence of sedative, atropine-like and cardiotropic effects, absence of tachyphylaxis and interaction with other medicines, absence of influence on ability to drive motor transport and complicated mechanisms. Pharmacokinetic properties of ebastine characterize the drug as a highly selective H1-histamine-blocker of long action, which can be taken regardless of meals. High therapeutic efficacy of ebastine in treatment of various allergic diseases and conditions has been confirmed by numerous clinical studies. Including the effectiveness of the drug in long-term courses of therapy, ebastin when taken for 1 year retains its antihistamine activity, which makes it possible to prescribe the drug for 3-12 months. Antihistamine and anti-inflammatory effects of ebastine allow to stop the main symptoms of allergy, as well as throat fart, coughing fits, olfactory disorders and skin peeling. Thus, the antihistamine drug ebastine has pharmacological characteristics with a high degree of compliance with the requirements for an "ideal" antihistamine drug.